Enhancing Students' Motivation and Learning Outcomes Through the Problem-Solving Learning Model at Elementary School - Fitriani Fitriani; Alfi Syahrin; Silvi Listia Dewi (STAI Hubbulwathan Duri, 2025)
Improving the quality of science learning requires effective teaching models, one of which is the problem-solving approach. This model not only enhances students' understanding of scientific concepts but also fosters higher motivation and improved academic outcomes. This quantitative study aimed to investigate the impact of the problem-solving learning model on students’ motivation and learning outcomes in science at SDN 6 Pegasing. The research employed a one-group pretest-posttest design within a pre-experimental framework. The sample consisted of 30 fifth-grade students. Data analysis was conducted using a paired sample t-test. Results indicated a statistically significant improvement in students’ science learning outcomes after the intervention, with a p-value of 0.001 (0.05). Similarly, students' motivation scores showed a notable increase, from a pre-test average of 71.13 to a post-test average of 89.60, also supported by a p-value of 0.001. These results suggest that the application of the problem-solving model led to measurable gains in both cognitive and motivational aspects of student learning. The findings confirm that the problem-solving learning model positively influences students' motivation and learning outcomes. By engaging in structured problem-solving activities, students were better able to grasp essential scientific concepts and sustain interest throughout the learning process. The application of the problem-solving model significantly enhances both motivation and learning outcomes in science education. Therefore, this model can serve as an effective pedagogical approach in primary science classrooms.